IMPLEMENTASI KURIKULUM MERDEKA DALAM PENGUATAN PROFIL PANCASILA DI SMA DHARMAWANITA BOARDING SCHOOL-KEDIRI, JAWA TIMUR - Kunaenih; Firdaus; Nadiah; Muhammad Syahdan Fachrurrozy; Sintia Putri Pangestu; Nisfe Jehan Apriani (Almarhalah: Jurnal Pendidikan Islam, 2024)
The project to strengthen the profile of Pancasila students is one of the projects implemented in the Merdeka curriculum, the implementation of which is different in each school. This research aims to find out how the implementation of the independent curriculum strengthens the profile of Pancasila in the school. This research method uses a descriptive qualitative approach. The results of this research were obtained from interviews and observations. Using interview instruments, this research conducted interviews with informants from schools consisting of school principals, teachers and students. Based on the results of this research, the implementation of the independent curriculum at SMA Dharma Wanita, Kediri, East Java has not been implemented comprehensively, but has only been implemented in grade 10. Meanwhile, grades 11 and 12 are still implementing the 2013 Curriculum, and are collaborating with the Putra Sampoerna Foundation (PSF) as an educational consultant to hold outreach and training at SMA Dharma Wanita, Kediri, East Java which discusses the independent curriculum, learning the independent curriculum and learning about P5 activities. Then, in its implementation, SMA Dharma Wanita formed a team of several teachers who were the driving force for creating the P5 project and teaching modules. The Independent Curriculum teaching module at SMA Dharma Wanita was created by adopting or adapting examples of teaching modules that have been created by the ministry and adapted to the school's capabilities.